Internal Motivation and Attitude in Implementation of Inclusive Education Program between General Education and PPKI Teachers - Idris, Nur Huda; Tahar, Mohd Mokhtar (Journal of ICSAR, 2023)
Collaboration between teachers of the Special Integration Education Program (PPKI) and general education teachers is a key factor in the successful implementation of the inclusive education. Internal motivation factors and the attitude of teachers involved in inclusive education are vital to ensure the smooth implementation of inclusive education. Therefore, the objective of this study is to identify the internal motivation and attitude toward collaboration between PPKI teachers and general education teachers in the implementation of inclusive education. This study is a survey study using quantitative methods. The theory used in this study is Glasser's Choice Theory. The instrument of this study is a questionnaire adapted from a thesis entitled A Case Study of Collaboration Between General Education Teachers and Special Education Teachers in a Southern Rural High School by Oassie Jean Daniels in 2017. This study involves PPKI teachers and general education teachers in a primary school with a Special Education  Integration Program of Learning Disabilities in the district of Pasir Gudang, Johor. The data was analysed using SPSS version 26 software. The findings of the study show that the highest mean score for internal motivation is a sense of belonging while the attitude towards collaboration is teacher cooperation and openness. There is a significant relationship between internal motivation and attitude toward collaboration between PPKI teachers and general education teachers in the implementation of inclusive education. In the future, this study can be conducted on a larger population and use different research theories.